Pseudomyxoma peritonei, cystadenoma mucinosum of the appendix and granulosa cell tumor of the ovary in a 54-year-old woman. A case report - Sobstyl, Małgorzata; Bednarek, Wiesława; Czekierdowski, Artur; Kondracka, Adrianna; Pawłowska-Wakowicz, Barbara; Kotarski, Jan (Menopause Review/Przegląd Menopauzalny, 2009)
The etiology of pseudomyxoma peritonei is unknown. There are several study reporting pseudomyxoma peritonei associated with the tumors of abdominal cavity, especially related with appendix at/or ovary. We reported case of pseudomyxoma peritonei associated with cystadenoma appendix and granulose cell tumor of the ovary in 54-year-old woman. Ultrasound showed a cystic tumor with solid area of the right ovary, size 9 cm. The tumor marker (Ca 125) was within the normal limit. Laparotomy was performed during which the following structures were diagnosed: normal size uterine body, bilaterally enlarged ovaries with the presence of mucinous cysts on their surface, 8 cm diameter tumor infiltrating appendix, in greater omentum presence of tumor like mucosal structures. Ascites was not present. The patient underwent total abdominal hysterectomy, bilateral salpingo-oophorectomy, omentectomy and appendectomy. The histopathological examination was describe pseudomyxoma peritonei, cystadenoma mucinosum of the appendix and granulose cell tumor of the right ovary. This case represented FIGO stage I. Pseudomyxoma peritonei may occur in patients with appendiceal mucoceles and ovarian tumor.